The temperature falls from 0 degrees to Negative 12 and one-fourth degrees in 3 and one-half hours. Which expression finds the change in temperature per hour?
Negative StartFraction 7 over 2 EndFraction divided by StartFraction 49 over 4 EndFraction
Negative StartFraction 7 over 2 EndFraction times StartFraction 49 over 4 EndFraction
Negative StartFraction 49 over 4 EndFraction times StartFraction 7 over 2 EndFraction
Negative StartFraction 49 over 4 EndFraction divided by StartFraction 7 over 2 EndFraction

Respuesta :

Answer:

yall need to stop lying Imao Negative StartFraction 49 over 4 EndFraction divided by StartFraction 7 over 2 EndFraction

Step-by-step explanation:

The expression that finds the change in temperature per hour for this considered case is given by: Option D: [tex]\dfrac{-47/4}{7/2}[/tex]

How to measure the rate of change of something as some other value changes?

Suppose that we have to measure the rate of change of y as x changes, then we have:

[tex]Rate = \dfrac{y_2 - y_1}{x_2 - x_1}[/tex]

where we have

[tex]\rm when \: x=x_1, y = y_1\\when\: x = x_2, y= y_2[/tex]

Remember that, we divide by the change in independent variable so that we get some idea of how much the dependent quantity changes as we change the independent quantity by 1 unit.

(5 change per 3 unit can be rewritten as 5/3 change per 1 unit)

For this case, we're specified that:

  • Initial temperature = 0 degrees.
  • Final temperature = [tex]-12 \dfrac{1}{4}[/tex] degrees.
  • Time taken for this change = [tex]3\dfrac{1}{2}[/tex] hours

Expressing final temperature in simple form:

[tex]-12\dfrac{1}{4} = -12 + \dfrac{1}{4} = \dfrac{-12 \times 4}{4} + \dfrac{1}{4} = \dfrac{-47}{4}[/tex]

Expressing time taken for the considered temperature change in simple forms:

[tex]3\dfrac{1}{2} = 3 + \dfrac{1}{2} = \dfrac{3 \times 2}{2} + \dfrac{1}{2} = \dfrac{7}{2}[/tex]

The temperature depends on time.

Suppose that:

x = time, y = temperature

Then, suppose that:

  • [tex]x_1[/tex] = Time when temperature was [tex]y_1 = 0[/tex] degrees.
  • [tex]x_2[/tex] = Time when temperature was [tex]y_2 = -\dfrac{47}{4}[/tex] degrees.

Then, the rate of change of temperature would be:

[tex]Rate = \dfrac{y_2 - y_1}{x_2 - x_1}[/tex]

The change in time is: [tex]x_2 - x_1 =\dfrac{7}{2}[/tex] (in hours).

Thus, we get:
[tex]Rate = \dfrac{y_2 - y_1}{x_2 - x_1} = \dfrac{-47/4 - 0}{7/2} = \dfrac{-47/4}{7/2}[/tex]

Thus, the expression that finds the change in temperature per hour for this considered case is given by: Option D: [tex]\dfrac{-47/4}{7/2}[/tex]

Learn more about rate of change here:

https://brainly.com/question/19167959

#SPJ2

ACCESS MORE